PENGARUH CURRENT RATIO RETURN ON ASSET DAN EARNING PER SHARE TERHADAP HARGA SAHAM STUDI KASUS PADA PERUSAHAAN PERTAMBANGAN SUBSEKTOR BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2018 - Titi Nurjanah; Suhardi Suhardi; Afrizal Afrizal (LPPM STIE PERTIBA Pangkalpinang, 2020)
This study aims to determine the effect of the Current Ratio, return on assets, and Earning Per Share variables on the Share Prices of Coal Subsector Mining Companies Listed on the Indonesia Stock Exchange 2014-2018. The research sample of 6 mining industries was obtained by purposive sampling technique. The data collection technique used is documentation. Data analysis was performed by panel data regression. The results showed that the Earning Per Share variable had a significant effect on stock prices, while the Current Ratio and Return on assets variables had no effect on stock prices. Further research is suggested to add variables or conduct research in other industries and use different methods.